2011
DOI: 10.1097/sih.0b013e31821687b3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Standardized Patient Checklist Item Accuracy and Performing Arts Experience

Abstract: : Results suggest that SPs with or without a performing arts background complete history taking and physical examination checklist items with high levels of precision. Therefore, SPs with and without performing arts experience can be recruited for high-stakes SP-based clinical skills examinations without sacrificing examination integrity or scoring accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Tamblyn et al (1990) noted that previous simulation and acting experience accounted for some variance in SP accuracy. However, in relation to recording accuracy, Langenau et al (2011) reported that SPs with previous performing arts experience achieved the same level of recording accuracy in medical student examinations as those without previous experience. It is apparent that future research on the impact of such experience on SP accuracy in portrayal of scenarios is required to assist in the planning and SP selection stages.…”
Section: Accuracymentioning
confidence: 98%
See 1 more Smart Citation
“…Tamblyn et al (1990) noted that previous simulation and acting experience accounted for some variance in SP accuracy. However, in relation to recording accuracy, Langenau et al (2011) reported that SPs with previous performing arts experience achieved the same level of recording accuracy in medical student examinations as those without previous experience. It is apparent that future research on the impact of such experience on SP accuracy in portrayal of scenarios is required to assist in the planning and SP selection stages.…”
Section: Accuracymentioning
confidence: 98%
“…A number of studies have investigated the impact of SP factors on their recording of student behaviours (Heine et al 2003, Langenau et al 2011, Wallace et al 1999, Wang et al 1996. Such investigations have taken place within the context of SPs taking a dual role: portraying a scenario and then rating a student's performance within the interview.…”
Section: Accuracymentioning
confidence: 99%
“…10 The OSCE is becoming the method of choice to assess the clinical skills of medical students and has been incorporated into high-stakes medical licensing examinations, such as the US Medical Licensing Examination Step 2 Test of Clinical Skills, the Medical Council of Canada's Qualifying Examination Part II, and the Comprehensive Osteopathic Medical Licensing Examination Level 2 Performance Evaluation. 11 Research has shown the reliability and feasibility of multiple OSCEs across various clinical specialties. 12 However, only a few OSCE tools are currently described in the otolaryngology literature, including one focused on hoarseness evaluation by Stewart et al, which used a similar methodology and employed a standardized patient (SP).…”
mentioning
confidence: 99%
“…OSCEs assess a variety of skills, such as history taking, physical examination, technical ability, professionalism, and communication 10 . The OSCE is becoming the method of choice to assess the clinical skills of medical students and has been incorporated into high‐stakes medical licensing examinations, such as the US Medical Licensing Examination Step 2 Test of Clinical Skills, the Medical Council of Canada’s Qualifying Examination Part II, and the Comprehensive Osteopathic Medical Licensing Examination Level 2 Performance Evaluation 11 . Research has shown the reliability and feasibility of multiple OSCEs across various clinical specialties 12 .…”
mentioning
confidence: 99%